Impact of Social Determinants of Health on Chronic Kidney Disease: A Review of Disparities in Renal Transplantation - Conner Lombardi (The University of Toledo, 2021)
Background: Striking disparity exists in the incidence and treatment of chronic kidney disease (CKD) secondary to individual social determinants of health.  Additionally, the uninsured, minority racial-ethnic groups, and Medicaid enrollees receive less nephrology care prior to being diagnosed with end-stage renal disease (ESRD). The most effective treatment for the management of kidney failure is kidney transplantation. This review addresses how social determinants of health impact the workup for patients with ESRD, with emphasis on the kidney transplant process.